2014
DOI: 10.1038/bjc.2014.312
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors in elderly patients with malignant pleural mesothelioma: results of a multicenter survey

Abstract: Background:The incidence of malignant pleural mesothelioma (MPM) in elderly patients is increasing. There are no specific guidelines for their management.Methods:The clinical records of elderly patients (⩾70 years old) with MPM referred from January 2005 to November 2011 to six Italian Centres were reviewed. Age, gender, histology, International Mesothelioma Interest Group (IMIG) stage, Eastern Cooperative Oncology Group Performance Status (ECOG-PS), Charlson Comorbidity Index (CCI) and treatment modalities we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
28
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 38 publications
5
28
1
Order By: Relevance
“…13 In this study, more than 90% of our patients received a pemetrexed-based first-line chemotherapy, and those who received more than 2 cycles of chemotherapy, if clinically stable, demonstrated improved survival. In our study, patients who had clinical benefit with first-line chemotherapy showed a 10 month improvement in median overall survival.…”
Section: Discussionmentioning
confidence: 72%
“…13 In this study, more than 90% of our patients received a pemetrexed-based first-line chemotherapy, and those who received more than 2 cycles of chemotherapy, if clinically stable, demonstrated improved survival. In our study, patients who had clinical benefit with first-line chemotherapy showed a 10 month improvement in median overall survival.…”
Section: Discussionmentioning
confidence: 72%
“…13 In fact, available data suggest that elderly patients with good functional status might obtain comparable benefits in terms of disease control rate and survival compared to their younger counterparts. 14 Whereas therapeutic nihilism might be the most obvious explanation for the apparent under treatment of the elderly, additional studies are warranted to fully understand the factors underlying the limited utilization of systemic therapy in the elderly mesothelioma population.…”
Section: Discussionmentioning
confidence: 99%
“…13 Due to a long latent stage, 58% of patients diagnosed with MPM are over the age of 70 years upon presentation, 4 and the incidence of elderly patients diagnosed with MPM globally is increasing. 510 Although increasing age has consistently been shown to be associated with worse survival, 3 there are very few studies that report specific outcomes among elderly patients. In particular, the survival benefit of surgery for elderly patients with MPM has not been clearly established.…”
Section: Introductionmentioning
confidence: 99%